Demographic Profile of NSTEMI (Non ST Elevation Myocardial Infarction) Patients & Association of ST-Segment Depression and Level of Troponin I with NSTEMI Patient’s In-Hospital Outcome - Zahid, Md Abu; Khan, HI Lutfur Rahman; Chowdhury, Abdul Wadud; Sabah, Khandker Md Nurush; Kabir, SM Eftar Zahan; Rahman, Md Hasanur; Hossain, Mofazzal; Khan, Tunaggina Afrin (Medicine Today, 2016)
Acute coronary syndrome (ACS) remains the leading cause of death in the developed world and second leading cause of death in developing countries. Elevated troponin levels and extent of ST-segment depressions are clinically important because they may act as an effective prognostic marker .This cross-sectional study has been designed to see the correlation of ST-segment depression and level of troponin I with in-hospital outcome of NSTEMI patients. The study was conducted in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka during the period of April, 2011- March, 2012. A total of 90 patients were selected by purposive sampling. In this study,the mean ±SD age of the patients was 55.9±9.1 years with a range of 36-80 years with a male -female ratio of 2:1.Over all dyslipidaemia was the most common risk factor present in 55(61.10%) patients followed by smoking in 48(53.3%) patients then obesity in 32(35.60%) then hypertension in 31(34.4%) patients. Troponin I level was significantly high in patients who developed acute LVF (10.36±7.4 vs 7.0124±6.8, p=.027), and cardiogenic shock (13.72±11.37 vs 8.64±7.35, p=.033). Troponin I was significantly high in patients who developed complication (10.72±8.84 vs 6.24±5.41, p=.005) than the patients who were discharged without complication. ST segment depression was significantly more in patients who developed acute LVF(1.07±1.63 vs.55±.74, p=.048). Logistic regression analysis of acute LVF with Troponin I and ST-segment depression showed that ST-segment depression and level of Troponin I were important correlates of acute LVF . Medicine Today 2015 Vol.27(2): 14-19